Balloon dilatation of congenital aortic valve stenosis in infants and children: short term and intermediate results. Issue 2 (August 1989) - Vogel, M; Benson, L N; Burrows, P; Smallhorn, J F; Freedom, R M
Abstract : Percutaneous balloon dilatation of the aortic valve was attempted in 25 consecutive patients with stenosis. The aortic valve diameters were normal for age. The balloon catheters were placed retrogradely, and their diameters were within 1-2 mm of the valve diameter and 3 (13 patients) or 6 cm (recent 12 patients) long. After dilatation the pressure gradients across the aortic valve were reduced significantly and the valve areas, measured in 10 patients, increased. Aortic regurgitation was detected in six patients before (grade I) the procedure and in 15 patients (6 grade I, 6 grade II, 3 grade III) after the procedure. In one patient the aortic valve could not be crossed and in three there was no reduction in the pressure drop. Nine patients have a sustained reduction in Doppler assessed gradients. There were vascular complications in 12 and these required surgical intervention in three patients. Balloon dilatation seems to be an effective short term palliative procedure in patients with congenital stenosis of the aortic valve.